إصدار وتداول الصكوك الإسلامية في سوق الأوراق المالية – تحديات ومتطلبات نجاحها في الجزائر- - غرداوي فاتح; غزازي عماد (جامعة الوادي University of Eloued, 2024)
تهدف هذه الدراسة الى توضيح ضوابط الشرعية لإصدار وتداول الصكوك الإسلامية في سوق الأوراق المالية بالإضافة إلى دراسة واقع سوق الصكوك الإسلامية في العالم وأبرز التحديات التي تواجهها، وفي الأخير دراسة إمكانية تفعيل الصكوك الإسلامية في بورصة الجزائر ومتطلبات نجاحها، وخلصت هذه الدراسة الى أن لابد من الإلتزام بضوابط شرعية عندإصدار الصكوك الإسلامية وتداولها ووجود بعض المعوقات والتحديات اهمها: غياب الإطار التشريعي والقانوني والتنظيمي، نقص الموارد البشرية المؤهلة وهذا يستدعي مجموعة من الحلول أبرزها: اختيار وتنمية الافراد، ضرورة توفر سوق رأس مال للمصارف الاسلامية، تعديل الهيكل التنظيمي للمصرف الاسلامي. This study aims to clarify the legal controls for issuing and trading Islamic Sukuks in the stock market, in addition to studying the reality of the Islamic Sukuk market in the world and the most prominent challenges it faces, and finally studying the possibility of activating Islamic Sukuks on the Algerian Stock Exchange and the requirements for their success. This study concluded that it is necessary to adhere to Sharia controls when issuing and trading Islamic Sukuks, and that there are some obstacles and challenges, the most important of which are: the absence of a legislative, legal and regulatory framework, the lack of qualified human resources, and this calls for a set of solutions, the most important of which are: selecting and developing individuals, the necessity of providing a capital market for Islamic banks, amending. Organizational structure of the Islamic bank.
Issuing and trading Islamic sukuks in the stock market -challenges and requirements for their success in Algeria
Keywords: الصكوك الإسلامية; سوق الأوراق المالية; إصدار الصكوك الإسلامية; الجزائر; تحديات الصكوك الإسلامية